Microwave-assisted upcycling of plastic waste to high-performance carbon anode for lithium-ion batteries - Muhammad Amirul, Aizat Mohd Abdah *; Fathihah Nabila, Mohammad Azlan *; Wong, Weng Pin *; Muhammad Norhaffis, Mustafa *; Rashmi, Walvekar; Khalid, Mohammad * (Elsevier, 2024)
The increasing demand for high-performance lithium-ion batteries (LIBs) has emphasized the need for affordable and sustainable materials, prompting the exploration of waste upcycling to address global sustainability challenges. In this study, we efficiently converted polypropylene (PP) plastic waste from used centrifuge tubes into activated polypropylene carbon (APC) using microwave-assisted pyrolysis. The synthesis of APC was optimized using response surface methodology/central composite design (RSM/CCD). Based on the RSM results, the optimal conditions for PP plastic conversion into carbon were determined as follows: HNO3 concentration of 3.5 M, microwave temperature of 230 °C, and holding time of 25 min. Under these conditions, the obtained intensity ratio of Id/Ig in PP carbon was 0.681 ± 0.013, with an error of 6.81 ± 0.013 % between predicted and actual values. The physicochemical studies, including FESEM-EDX, XRD, and Raman spectroscopy, confirmed the successful synthesis of APC samples. The APC 800 material exhibited a well-organized three-dimensional structure characterized by large pores and mesopores, enabling fast ion transport in the electrode. As a result, the APC 800 electrode demonstrated an initial discharge capacity of 381.0 mAh/g, an improved initial coulombic efficiency of 85.1%, and excellent cycling stability after 100 cycles. Notably, the APC 800 electrode displayed remarkable rate performance, showing a reversible capacity of 355.1 mAh/g when the current density was reset to 0.2 A/g, highlighting its high electrochemical reversibility. The outstanding characteristics of APC 800 as an anode electrode material for high-performance lithium-ion batteries suggest a promising future for its application in the field.